Differential Expression of HSP90β in MDA-MB-231 and MCF-7 Cell Lines after Treatment with Doxorubicin - Fereshte Jokar; Javad Amini Mahabadi; Morteza Salimian; Aliakbar Taherian; Seyyed Mohammad Gheibi Hayat; Amirhossein Sahebkar; Mohammad Ali Atlasi (Korean Pharmacopuncture Institute, 2019)
Background: Breast cancer is a complex, heterogeneous disease and one of the most common malignancies in women worldwide. The efficacy of chemotherapy as an important breast cancer treatment option has been severely limited because of the inherent or acquired resistance of cancer cells. The molecular chaperone heat shock protein 90 (HSP90) upregulated in response to cellular stress is required for functions such as conformational maturation, activation and stability in more than 200 client proteins, mostly of the signaling type. In this study, the expression of HSP90 isoforms including HSP90α and HSP90β in breast cancer cell lines before and after treatment with doxorubicin (DOX) was assessed. Material and Methods: The cell cytotoxicity of DOX in MDA-MB-231 and MCF-7 cell lines was determined using the MTT assay. Immunofluorescence and western blotting techniques were used to determine the expression of HSP90β in the cell lines before and after DOX treatment. Immunofluorescence was also conducted to ascertain the expression of HSP90α. Results: The MTT assay results showed that the MDA-MB- 231 cells (IC50=14.521 μM) were more sensitive than the MCF-7 cells (IC50=16.3315 μM) to DOX. The immunofluorescence results indicated that the expression of HSP90α in both cell lines decreased after exposure to DOX. The western blot and immunofluorescence analyses showed that HSP90β expression decreased in the MCF-7 cells but increased in the MDA-MB- 231 cells after DOX treatment. Conclusion: The obtained results suggested that HSP90α and HSP90β expression levels were reduced in the MCF-7 cells after exposure to DOX. In the MDA-MB-231 cells, HSP90α expression was reduced while HSP90β was found to be overexpressed following DOX treatment.